ANALYTICAL STUDY USING X-RAY DIFFRACTION METHODS AND HARDNESS TEST FOR LEAD-TIN ALLOY - Abdul Alrazaaq, Ali (Iraqi Journal of Science, 2024)
Structural and mechanical properties for lead-tin alloy have been studied byemploying the X-Ray diffraction methods and Vickers microhardness test. Threesamples were obtained, the first standard lead- tin sample, the second form recyleledingot of the alloy and the third prepared from the powder of recyeled ingot that wasvacuum capsuled and treated at 800 oC for 3 hours.The X-Ray diffraction spectra ofboth recycled ingot and prepared alloy showed the appearance of a new stable phaseof tin oxide (SnO) with the tin (Sn) phase appear in preferred orientation dictated bythe technical route of preparation. Furthermore the grain size of lead and tin phaseswere nearly identical though in the tin oxide phase, the grain size decreases to halfof that to lead and tin due to the defective nature of the SnO phase. Microhardnesstest on the three samples reveal an increase in the mechanical strength as a result ofthe presence of tin oxide phase that acts as a mechanical strengthener via dispersionstrengthening.